Exploring Social Imagination, Emotion Regulation And Behavioral-emotional Problems: A Comparison Between Adhd At Risk And Typical Preschoolers - Fang, Fang (2024)
This study embarks on an investigation of emotion regulation, social imagination, and behavioral-emotional problems in typically developing preschoolers and those at risk for Attention Deficit Hyperactivity Disorder (ADHD). Adopting a mixed-method research approach, the study uniquely focuses on preschoolers' social imagination, a critical cognitive skill for understanding others' thoughts, feeling and intentions. To address the lack of quantitative methods in evaluating interactions with wordless picture books, a novel TFI Analysis Framework was proposed and tested in this study. The study comprises a pilot study with one preschooler, followed by two main studies: Study 1 with 34 typically developing preschoolers and Study 2 with 11 preschoolers at risk of ADHD. using a wordless picture book to elicit qualitative data, which is then systematically transformed into structured quantitative data through the TFI Analysis Framework. This approach proves effective in revealing universal patterns in social imagination development among preschoolers. For typically developing preschoolers, the findings revealed a significant correlation between enhanced social imagination and improved emotion regulation, which consequently correlates with fewer behavioralemotional problems. It was also found that preschoolers at risk for ADHD exhibited distinct patterns in emotion regulation and behavioral-emotional challenges.